Intraspecific genetic diversity of the fish-infecting microsporidian parasite Pseudokabatana alburnus (Microsporidia) - Weng, Meiqi; Zhang, Xintong; Xin, Zhaozhe; Xue, Sijia; Zhang, Qianqian; Li, Aihua; Zhang, Jinyong (Frontiers in Microbiology, 2023)
Pseudokabatana alburnus is a xenoma-forming fish microsporidium, firstly described from the liver of the Culter alburnus from Poyang Lake in China. In the present study, P. alburnus was firstly reported from the ovary of 6 other East Asian minnows, including Squaliobarbus curriculus, Hemiculter leucisculus, Cultrichthys erythropterus, Pseudolaubuca engraulis, Toxabramis swinhonis, and Elopichthys bambusa. Genetic analysis revealed high sequence diversity in the ribosomal internal transcribed spacer region (ITS) and the largest subunit of RNA polymerase II (Rpb1) loci of P. alburnus isolated from different hosts and locations. The variation of Rpb1 mainly occurred in the 1477-1737 bp regions. The presence of a wide variety of Rpb1 haplotypes within a single fish host, together with evidence of genetic recombination suggested that P. alburnus may have the intergenomic variation and sexual reproduction might be present in other hosts (possibly freshwater shrimp). Phylogenetic analysis and population genetic analysis showed that there was no geographical population divergence for P. alburnus. Homogeneity and high variability of ITS sequences indicates that ITS may be a suitable molecular marker to distinguish different P. alburnus isolates. Our data confirm the broad geographical distribution and host range of P. alburnus in the middle and lower reaches of the Yangtze River. Additionally, we emendated the genus Pseudokabatana to exclude the infection site, liver as one of the taxonomic criteria, and proposed that fish ovary was be the general infection site of P. alburnus.